ANALISIS PENGARUH PERGANTIAN KANTOR AKUNTAN PUBLIK DAN OPINI AUDIT TERHADAP REAKSI PASAR - Ngaijan ngaijan (UNIMAR AMNI Semarang, 2017)
The enactment of the Finance Minister regarding policy changes KAP rotation over a certain period , makes the phenomenon interesting turn of auditors or accounting firm to be assessed . This is because many factors can affect the turnover auditor or accounting firm that carried out by the company and it can be influenced by external factors and internal factors . Auditor turnover can also be a trigger for the market reaction.The study population is a company registered in LQ 45 in 2008-2010 . The sample using purposive sampling method, in which the sample is selected based on criteria teitentu . The criteria used in selecting the sample of this study are as follows : ( 1 ) Company registered in LQ 45 during the years 2008-2010. ( 2 ) the Company's audited keuanganya reports from 2008-2010 that included the name of the firm or its auditors and statements contained Opinion of KAP about the fairness of financial statements . ( 3 ) The company has a complete stock of data available on the IDX database during 2008-2010 . Data analysis was performed using multiple linear regression.Results of hypothesis testing concluded that : ( 1 ) Substitution of auditors ( from Big 4 to non- Big 4 and otherwise ) affects the market reaction . Substitution of the big 4 to non- Big 4 responded negatively by the market and instead turn of non big 4 big 4 responded to positively by the market . ( 2 ) audit opinion affect the market reaction , firms with audit opinion other than